Segmental neurofibromatosis type 1. Differences between the childhood and adult form - Pisani, V.; Caniglia, A; Bonifazi, E. (European Journal of Pediatric Dermatology, 2012)
Like many other inherited skin disorders with autosomal dominant transmission also neurofibromatosis type 1 (NF1) can manifest itself in a segmental distribution, due to a not early post-zygotic mutation of the gene responsible for NF1. In this paper, we revised the clinical data of 11 cases of childhood segmental NF1. While in adult segmental NF1 prevail forms characterized by the exclusive presence of neurofibromas, in children prevail forms characterized only by café-au-lait macules (CALMs). Both in children and adults is rare to observe the simultaneous presence of café-au-lait macules and neurofibromas. This behavior is probably due to the fact that the CALMs and neurofibromas are due to different mutations, which affect different cell lines, particularly the fibroblast in CALMs and the Schwann cell in neurofibromas.